Murmansk Arctic State University - Scientific and Educational Center of the Murmansk Region - Georgii G. Gogoberidze; Maria A. Knyazeva; Ekaterina A. Rumiantseva (Moscow Polytechnic University, 2019)
The paper addresses the role of universities in the generation, use and dissemination of knowledge, analyzes principles and ways to develop science and education at universities. It is emphasized that the University is becoming an active player not only in training, but also in the production of a new knowledge, in its dissemination and implementation through innovation. At the same time, it is necessary to note that the conditions of the Far North impose a unique specificity on the work of the University and its scientific and innovative activities.For Murmansk Arctic State University (MASU), scientific and research work is one of the most dynamically developing components that create development potential. The paper presents the range of MASU's scientific activities which includes 3 main spheres: natural science, technical science, social science, and Humanities. The authors dwell on the students' and postgraduates' scientific activities, consider the youth scientific organizational structure.As a flagship University, MASU is implementing a strategic development project "MASU is Scientific and Technological Hub of the Region" formed with the direct support of the Government of the Murmansk region. Within the framework of the project, an information and analytical platform was created in MASU under the partnership with Kola Science Center RAS (IAP MASU-KSC). This platform is an integrating consulting mechanism including a set of technological, commercial and marketing solutions for the development and implementation of innovative products and technologies in organizations operating in the field of ensuring a comfortable human presence in the Far North.As one of the priority goals of the strategic development of the University, the trajectory of the Arctic scientific and educational center (SEC) creation on the basis of MASU is highlighted. The key areas and ways to improve the efficiency of scientific and educational activities of MASU, as well as the expected results of the SEC are considered.